Genetic susceptibility to total hip arthroplasty failure: a preliminary study on the influence of matrix metalloproteinase 1, interleukin 6 polymorphisms and vitamin D receptor - Malik, M H A (BMJ Group, 2007)
BACKGROUND: Matrix metalloproteinase (MMP)1, interleukin(IL)6 and vitamin D receptor (VDR) have been implicated in the biological cascade of events initiated by particulate wear debris and bacterial infection, resulting in periprosthetic bone loss around loosened total hip replacements (THRs). The individual responses to such stimuli may be dictated by genetic variation. OBJECTIVE: To study the effect of single‐nucleotide polymorphisms (SNPs) within these candidate genes. METHODS: A case–control study of the MMP1, IL6 and VDR genes was performed for possible association with deep sepsis or aseptic loosening. All cases included in the study were Caucasian patients with osteoarthritis who had received a cemented Charnley total hip arthroplasty (THA) and polyethylene acetabular cup. Cases consisted of 91 patients with early aseptic loosening and 71 patients with microbiological evidence of deep infection on surgery. Controls consisted of 150 patients with THAs that were clinically asymptomatic for over 10 years and showed no radiographic features of aseptic loosening. DNA samples from all individuals were genotyped using Taqman allelic discrimination. RESULTS: The C allele (p = 0.001; OR = 3.27; 95% CI 2.21 to 4.83) and C/C genotype (p = 0.001) for the MMP1 SNP were highly associated with aseptic failure when compared with controls. No statistically significant relationships were found between aseptic loosening and the MMP2, MMP4, IL6 –174 or VDRL SNPs. The T allele (p = 0.007; OR = 1.76; 95% CI 1.16 to 2.66) and T/T genotype (p = 0.028) for VDR‐T were statistically associated with osteolysis owing to deep infection as compared with controls. No statistically significant relationship was found between septic failure and any of the other SNPs examined in this study. CONCLUSIONS: Aseptic loosening and possibly deep infection of THR may be due to the genetic influence of candidate susceptibility genes. SNP markers may serve as predictors of implant survival and aid in pharmacogenomic prevention of THR failure.